Characterization of treated empty fruit bunches by thermogravimetric analysis (TGA) - Abdul Rahman Aizuddin; Abdullah Nurhayati (E3S Web of Conferences)
This research investigates the thermal degradation characteristics of treated empty fruit bunches (EFB) using thermogravimetric analysis (TGA), contributing to circular economy promotion by encouraging the use of agricultural by-products in the energy sector. EFB feedstock was prepared by immersing 100g of residue in 1.8 liters of distilled water for 40 minutes at room temperature (~30°C). Results show that this treatment reduced ash content by approximately 2.74 wt%. TGA data reveals that untreated EFB exhibited greater weight loss compared to treated EFB, with the latter showing shifted decomposition processes at higher thermal degradation temperatures. The study explores ash’s catalytic influence, providing insights into weight loss patterns and decomposition temperature ranges. This enhanced understanding of biomass behavior provides valuable data for optimizing biomass-based energy systems, further advancing sustainable energy solutions and resource efficiency.